Mudhohi's decision to implement qurban in zakat institutions : a case study in Rumah Zakat institution - Ifa Hanifia Senjiati; Yadi Wahyudin (Indonesian Journal of Islamic Economics Research, 2020)
There has been a decline in animal sacrifice in 2012 at LAZ Rumah Zakat. There is a phenomenon that customers are not satisfied with Rumah Zakat services. Thus several factors can influence mudhohi's decision to sacrifice in zakat institutions. Based on these problems the formulation of the research problem is how mudhohi sacrifices decisions at zakat institutions. The research method used is a qualitative method with a descriptive analysis approach. Data collection techniques with interviews to 100 mudhohi. The result is that mudhohi's decision to sacrifice at Rumah Zakat is 93% mudhohi will sacrifice again. Mudhohi's decision to make sacrifices at Rumah Zakat is due to the longer value of superqurban benefits, distribution throughout the country, offering affordable prices, product innovation in the form of corned beef and rendang cans, simple processes, and voucher offers.